Portugals trees of public interest: their role in botany awareness - Lopes,Raquel Pires (2019)
Based on the classification processes, from 1939 to 2012, of the National Registry for Trees of Public Interest, from the Institute for Nature Conservation and Forests, it was verified that of the 278 municipalities, corresponding to the five Regions of Tourism of mainland Portugal, 130 municipalities do not have classification processes. Considering that is an environmental but also a social gap, the authors understand it is necessary to contribute to the social understanding of monumental trees through the promotion of scientific culture in botany, as an important means to emphasize its value as an endogenous differentiation element of each region. It is also intended to mobilize the general public, to identify and propose the classification of trees with monumental characteristics.